The Circular Economy Model for Electronic Waste (E-Waste) Management in Indonesia: A Review of Policies and Best Practices - I Putu Astawa; Ethan Tan; Marcus Tan (Journal of Multidisciplinary Sustainability Asean, 2025)
Background. Electronic waste (e-waste) has become one of the fastest-growing waste streams in Indonesia as rapid digitalization, increased consumer demand for electronic devices, and limited recycling infrastructure create significant environmental and public health challenges. Current disposal patterns—dominated by informal collection, open burning, and landfilling—pose risks related to soil contamination, toxic emissions, and exposure to hazardous substances such as lead, cadmium, and mercury. Purpose. This study aims to review national policies, regulatory frameworks, and best practices related to e-waste management in Indonesia through the conceptual lens of the circular economy. Method. The research employs a qualitative literature review design, synthesizing scholarly articles, government documents, international reports, and case-based analyses of e-waste management initiatives. Comparative analysis is used to identify gaps between policy intentions and implementation outcomes while highlighting successful practices at both national and regional levels. Results. Results show that CE-based initiatives—such as formal recycling facilities, producer take-back programs, and repair–reuse ecosystems—have begun to emerge but face barriers related to limited institutional capacity, low public awareness, and dominance of the informal sector. Conclusion. The study concludes that strengthening national coordination, scaling up CE-driven business models, and integrating community participation are essential for Indonesia to achieve sustainable e-waste management aligned with circular economy principles.